Women's rights in Islam - Mohd Zin, Najibah (Sweet and Maxwell Asia, 2012)
Women's rights in Islam have remained a controversial subject for decades, partly contributed by misconceptions in translating the law into practical reality. In another dimension; many cultural practices commonly practised by Muslims; particularly in Muslim countries often reflect negative treatment towards women. Therefore, this chapter will focus on the fundamental aspects of women's rights based on the premise that Islamic law has a comprehensive set of legal frameworks regulating women in elevating and determining their status in society. The study includes contextual analysis of these principles when examining their practicality in the modem context. Reference to international instruments is made to further support the arguments and comparatively assess their compatibility with the status of women in Islam. Primary sources of Islamic law will be the main references with further illustrations and exegesis from legal texts of acceptable standards in Islamic law research. Writings of modern scholars will be referred to as secondary sources which represent contemporary vieivs on how Islamic la,v treats women